Pengaruh Kompetensi Kewirausahaan Terhadap Keunggulan Bersaing (Studi Pada Industri Kreatif Sepatu Cibaduyut Kota Bandung) - Ivon Sandya Sari Putri; Destany, Zessy Rizkia; Suhaeni, Tintin (Jurnal Riset Bisnis dan Investasi, 2022)
The Cibaduyut shoe industry is one of the creative industries in the city of Bandung which has experienced a decline in turnover, this happens because there are several problems related to the entrepreneurial competence of entrepreneurs. In addition, the decline in turnover illustrates that Cibaduyut Shoes are not able to compete with its competitors. The purpose of this study to determine entrepreneurial competence, competitive advantage, and determine the effect of entrepreneurial competence on competitive advantage in the Cibaduyut shoe industry. The research method uses a descriptive survey with a quantitative approach and simple regression analysis. The sample of this study was 122 respondents consisting of owners and employees. The results showed that the entrepreneurial competence and competitive advantage of the Cibaduyut Shoes Industry were in the good category. Then it is known there is a positive and significant influence between the variables of entrepreneurial competence on competitive advantage of 13.8%.